Narratives and crime. Exploring the differences between desisters and persistent offenders (Delito y Sociedad, 2021)
The «narrative theory» stands that the linguistic and cognitive processes that guide autobiographies have the power to structure memory, generating effects for the future. This work applies narrative analysis to in-depth interviews with 96 people (men and women) who were in different stages of their criminal trajectories. The results show that, while the discourses of those who underwent a religious conversion have characteristics of what Maruna (2001) describes as «redemption scripts», they lack the dimension of internality and stability. On the other hand, the «secular desister» elaborate discourses linked to the «burn-out syndrome» characteristic of the ontogenetic perspective. Finally, the persistent offenders’ self-narratives are similar to the «condemnation scripts», even though they tend to place the causes of their adversities on external factors.
Keywords: Explanatory style; Criminal careers; Narratives; Desistance